Medical angioplasty - Hope and expectations: An optimistic overview - Mohammed F Abdul-Mohsen (Journal of Family and Community Medicine, 2011)
Primary and secondary prevention of cardiovascular diseases (CVD) are markedly overlooked worldwide. The use of these kinds of preventive methods will greatly improve outcome of or even reverse major CVD, especially coronary atherosclerosis. Comprehensive lifestyle changes combined with aggressive medical therapy [lipid lowering agents "statins", antiplatelet agents, beta-blockers and angiotensin-converting enzyme inhibitors] for patients suffering from coronary heart disease significantly reduce all major adverse cardiovascular events (MACE), especially in those with stable coronary artery disease (CAD), even if their coronary lesions are significant. The main mechanistic pathways for the significant reduction of MACE are: Stabilization of atheromatous plaques through endothelial function reparation, strengthening of the fibrous cap of the atheromatous plaque and reduction of atheroma burden, i.e., reversal of the process of coronary artery stenosis, the great dream of "medical angioplasty". Despite the compelling data indicating the great beneficial effects of both primary and secondary prevention of coronary atherosclerosis, the US national survey data reveals that only a minority of patients eligible by guidelines for these therapies in fact receive them. Hence, we strongly believe that our main duties as cardiologists is to improve the up-to-date knowledge of the practicing physicians about utility of aggressive medical therapy for both prevention and reversal of CVD, and also to promote useful primary and secondary prevention programs among physicians and patients. Meanwhile, further improvement and refinement of the current therapeutic modalities and introduction of new modalities for the management of lipid parameters other than LDL-C, such as HDL-C, triglyceride, lipoprotein (a), LDL particle size and susceptibility to oxidation may add further favourable effects in prevention and reversal of atherosclerotic process. Cardiologists should be just as aggressive with prevention as many have been with intervention. This optimistic overview is a valley cry to all practicing physicians; please depart from usual methods of intervention to preventive strategies which are largely overlooked.